Study on Preparation, SLS and Post-Process of ZrO Coated Powder - Xia, Sijie (2016)
A novel method named dissolution-precipitation process was used to prepare zirconia (ZrO2) ceramic composite powder. Nylon 12 was used as a binder to be coated on the surface of ZrO2 powder. The coated powder obtained by dissolution-precipitation process is more uniform and suitable for selective laser sintering. SLS optimized process parameters were determined as follows: laser power 5.5W, scanning speed 2000mm/s, scanning space 0.1mm, and layer thickness 0.1mm. The law of properties of SLS parts with pressure of cold isostatic pressure was studied. The reasonable post-process of cold isostatic pressing/debinding/furnace sintering was carried out. Bending strength and relative density of SLS parts were greatly enhanced after the post-process.